Synthesis of carbon modified titanium dioxide photocatalysts for removal of phenol - Mohd. Hatta, Mohd. Hayrie (2014)
Titanium dioxide (TiO2) has been recognized as an excellent photocatalyst, but lack adsorption capability. One of the suitable approaches to solve the problem is to introduce carbon materials to TiO2, through a simple process and only involve low cost precursors. In this study, carbon modified TiO2 was synthesized by using modified sol-gel method in the presence of acetyl acetone as the chelating ligand. Two carbon precursors of dichloromethane and carbon nanotubes (CNT) were used and the samples were denoted as DCM-TiO2 and CNT-TiO2, respectively. X-ray diffraction patterns showed that the addition of dichloromethane induced the formation of rutile phase in TiO2, while addition of CNT maintains the anatase phase of TiO2. Scanning electron microscope and field emission scanning electron microscope revealed the unaffected morphology of TiO2 after addition of the carbon precursors. The presence of carbon species was confirmed by diffuse reflectance ultraviolet visible spectroscopy and elemental dispersive X-ray analysis especially on samples with high loading of carbon precursors. The photocatalytic removal of phenol was carried out under UV light irradiation at room temperature for 24 hours. It was confirmed that all DCM-TiO2 and CNT-TiO2 series showed better adsorption and photocatalytic activity than the TiO2. The best catalyst for each series, which were 3% DCM-TiO2 and 5% CNT-TiO2, gave 72% and 68% phenol removal, respectively, while TiO2 showed only 17% phenol removal. Adsorption was proposed to be the important factor for the high activity. Since 3% DCM-TiO2 showed slightly faster rate constant than the 5% CNT-TiO2, it was proposed that the use of dichloromethane as carbon precursor and modified sol-gel as the simple method would be an alternative good method to prepare highly active carbon modified TiO2 photocatalysts.